The Influence of Fish Oil Supplementation in BSF (Black Soldier Fly) Larvae Growth Medium as an Omega-3 Source through Mixed Fermentation of Blood and Tofu on BSF Maggot Production and Its Nutritional Composition - Rido, Muhammad; Harnentis; Montesqrit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aims to evaluate the effect of incorporating fish oil as an omega-3 source on BSF maggot meal's production and nutritional composition when cultivated in a growth medium based on the mixed fermentation of ruminant blood and tofu. The study utilized BSF eggs, fresh blood, tofu, Probio_FM, and sardine fish oil. An experimental design was implemented, consisting of four treatment groups with three replications, following a completely randomized design (CRD). The treatments involved varying levels of fish oil supplementation in the BSF larvae growth medium: 0 percent (control), 2 percent, 4 percent, and 8 percent. The measured parameters included BSF maggot production and the nutritional content of BSF maggot meal. The analysis of variance (ANOVA) revealed that fish oil supplementation in the fermented blood and tofu growth medium did not significantly affect (P > 0.05) BSF maggot production. However, it had a significant effect (P < 0.05) on crude ash content and a highly significant effect (P < 0.01) on dry matter, crude protein, and crude fat content in BSF maggot meal. Supplementing fish oil at a 4 percent level resulted in a BSF maggot yield of 126.50 grams, with a dry matter content of 96.69 percent, crude protein at 32.35 percent, crude fat at 33.04 percent, and ash content at 6.22 percent.